2007
DOI: 10.1016/j.psychsport.2006.05.003
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of an identity: A qualitative exploration of retirement from women's artistic gymnastics

Abstract: This study examined among a sample of elite athletes the contention that the pursuit of performance excellence can hinder the formation of self-identity and that this, in turn, can lead to adaptation difficulties when an individual retires from sport. As these problems are known to be pronounced in women's artistic gymnastics due to the young ages at which participants begin and end their competitive careers, the experiences of five former female gymnasts were studied. Respondents participated in retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
147
2
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 26 publications
(51 reference statements)
10
147
2
14
Order By: Relevance
“…This built rapport, allowing participants to discuss a topic that was assumed to be relatively straightforward. Congruent with previous qualitative studies of retirement (Lavallee & Robinson, 2007), the schedule traced participants' experiences of retirement from a temporal perspective, gathering information on their life as an elite gymnast …”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…This built rapport, allowing participants to discuss a topic that was assumed to be relatively straightforward. Congruent with previous qualitative studies of retirement (Lavallee & Robinson, 2007), the schedule traced participants' experiences of retirement from a temporal perspective, gathering information on their life as an elite gymnast …”
Section: Instrumentmentioning
confidence: 99%
“…This is particularly pertinent in sports such as women's gymnastics, because the nature of elite gymnastics compels the athletes to "maximize their career into the years before puberty" (Kerr & Dacyshyn, 2000, p.127), the very years assigned to exploration and identity development. Accordingly, identity conflict has been strongly associated with retirement from elite gymnastics (Kerr & Dacyshyn, 2000;Lavallee & Robinson, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some IPA researchers even indicate prior to interview the precise areas participants will be 'required' to expand upon (e.g. Lavallee and Robinson, 2007). In a literature review of IPA-based research in health psychology, Brocki and Wearden (2006: 91) found that IPA interviews were often designed on the basis of extant research findings, theory or models, even including positivistic and quantitative work (e.g.…”
Section: Interpretative Phenomenological Analysis (Ipa): Caveatmentioning
confidence: 99%
“…De nombreux auteurs se revendiquant du courant de la psychosociologie ont défini une série d'éléments qui permettent d'envisager cette après-carrière de manière harmonieuse : une fin de carrière volontaire (Cecic Erpic, Wylleman & Zupanovic, 2004 ;Young, Pearce, Kane & Pain, 2006), une reconversion planifiée (Stambulova, Stephan & Jäphag, 2007), une identité socialement diversifiée et non pas uniquement centrée sur le rôle de l'athlète (Lavallee & Robinson, 2007), ainsi qu'un fort soutien social (Sinclair & Orlick, 1993). Cette recherche souhaite identifier, en amont, les processus susceptibles de mettre en péril la réalisation des éléments qui viennent d'être cités, en particulier la préparation de l'après-carrière des joueurs.…”
Section: Introductionunclassified